In a Methotrexate-Induced Model of Intestinal Mucositis, Olmesartan Reduced Inflammation and Induced Enteropathy Characterized by Severe Diarrhea, Weight Loss, and Reduced Sucrose Activity - Araújo, Aurigena Antunes de (2015)
The aim of this study was to evaluate the effect of olmesartan (OLME), an angiotensin II receptor antagonist, on an intestinal mucositis model. Briefly, daily intraperitoneal (i.p.) injections of methotrexate (MTX) 7 mg/kg were administered to rats on 3 consecutive days. A subset of these rats was also pretreated with oral administration of OLME (0.5, 1.0, or 5.0 mg/kg) or vehicle as a control 30 min prior to MTX injection. Body weight, feces scoring, and death were recorded daily. On day 4, the rats were killed, and intestinal tissues were assayed for levels of interleukin (IL)-1β and tumor necrosis factor (TNF)-α, myeloperoxidase and sucrose activity, and histopathological findings. A significant reduction in body weight was observed in the MTX+1.0 mg/kg OLME group (p<0.01). The feces scores for the MTX+0.5 mg/kg OLME and MTX+5.0 mg/kg OLME groups were also significantly higher (p<0.001). Sucrose activity was reduced in all groups treated with OLME (p<0.05). Treatment with MTX+OLM at all doses resulted in reduced inflammatory infiltration, ulcerations, vasodilation, and hemorrhagic areas (p<0.05), as well as reduced concentrations of myeloperoxidase (p<0.001). The IL-1β and TNF-α levels were decreased in the MTX+OLME 5.0 mg/kg (p<0.01 and p<0.05, respectively) compared with the MTX-alone group. Overall, antiinflammatory activity was observed in rats with MTX-induced intestinal mucositis that were administered OLME. However, further studies are needed to elucidate the adverse effects of OLME.